Glutamate-Cysteine Ligase Catalytic Subunit Attenuated Hepatitis C Virus-Related Liver Fibrosis and Suppressed Endoplasmic Reticulum Stress - Fu, Na; Li, Dongdong; Li, Wencong; Zhao, Wen; Zhang, Siyu; Liu, Lingdi; Zhao, Suxian; Du, Jinghua; Kong, Lingbo; Wang, Rongqi; Zhang, Yuguo; Nan, Yuemin (Frontiers in Molecular Biosciences, 2020)
The study aimed to clarify the role and molecular mechanism of glutamate-cysteine ligase catalytic subunit (GCLC) in modulating Hepatitis C virus (HCV)-related liver fibrosis. Twenty patients with HCV-related liver fibrosis and 15 healthy controls were enrolled. Differentially expressed plasma mRNAs were detected by digital gene expression profile analysis and validated by qRT-PCR. Hepatic histopathology was observed by H&E and Masson stained liver sections. The mRNA and protein expression of GCLC, endoplasmic reticulum (ER) stress markers, inflammatory and fibrogenic factors were detected in liver tissues from patients with HCV-related hepatic fibrosis and HCV core protein-expressing LX-2. The GCLC-overexpressing LX-2 were established by transfecting puc19-GCLC plasmid. Then, glutathione and reactive oxygen species (ROS) levels were measured respectively by spectrophotometric diagnostic kit and dihydrodichlorofluorescein diacetate kit. GCLC were dramatically down-regulated in HCV-related fibrotic livers and activated HSCs, which companied with up-regulation of ER stress-related genes, including inositol-requiring 1 (IRE1) and glucose-regulated protein 78 (GRP78). Also, the proinflammatory and profibrogenic gene, including nuclear factor kappa B (NF-κB), tumor necrosis factor α (TNFα) and transforming growth factor 1(TGFβ1) was highly upregulated. Overexpression of GCLC in hepatic stellate cells could suppress α-SMA and collagen I expression, produce hepatic GSH and reduce ROS, and down-regulate IRE1, GRP78, NF-κB, TNF-α, and TGFβ1 expression. GCLC was a negative regulatory factor in the development of HCV-related liver fibrosis and might be a potential therapeutic target for liver fibrosis.